Copper enhances cellular and network excitabilities, and improves temporal processing in the rat hippocampus. (25th November 2015) - Maureira, Carlos; Letelier, Juan Carlos; Alvarez, Osvaldo; Delgado, Ricardo; Vergara, Cecilia
Abstract: Copper, an ion with many important metabolic functions, has also been proposed to have a role as modulator on neuronal function, mostly based on its effects on voltage‐ and neurotransmitter‐gated conductance as well as on neurological symptoms of patients with altered copper homeostasis. Nevertheless, the mechanisms by which copper exerts its neuromodulatory effects have not been clearly established in a functional neuronal network. Using rat hippocampus slices as a neuronal network model, the effects of copper in the range of 10–100 nm were tested on the intrinsic, synaptic and network properties of the CA1 region. Most of the previously described effects of this cation were in the micromolar range of copper concentrations. The current results indicate that copper is a multifaceted neuromodulator, having effects that may be grouped into two categories: (i) activity enhancement, by modulating synaptic communication and action potential (AP) conductances; and (ii) temporal processing and correlation extraction, by improving reliability and depressing inhibition. Specifically it was found that copper hyperpolarizes AP firing threshold, enhances neuronal and network excitability, modifies CA3–CA1 pathway gain, enhances the frequency of spontaneous synaptic events, decreases inhibitory network activity, and improves AP timing reliability. Moreover, copper chelation by bathocuproine decreases spontaneous network spiking activity. These results allow the proposal that copper affects the network activity from cellular to circuit levels on a moment‐by‐moment basis, and should be considered a crucial functional component of hippocampal neuronal circuitry. Abstract : We document copper's operational closure conveying synaptic, action potential and network activity modulations. Cu 2+ at nm range, amplify signaling through the hippocampal network with no alterations in jittering but improving reliability of spike trains. In excess, Cu 2+ may induce a plethora of redox‐related deleterious effects; its deficit in turn will compromise the gain of this operational closure. We propose this mechanism for Wilson and Menkes neurological conditions.